Age-related changes of the innate immune system of the palatine tonsil in a healthy cohort - Andreas, Nico; Geißler, Katharina; Priese, Juliane; Guntinas-Lichius, Orlando; Kamradt, Thomas (Frontiers in Immunology, 2023)
Although tonsillectomy is performed frequently, the role of palatine tonsils in life long immune protection or tolerance is still debated and the consequences of their removal for the immune system are of general interest. We analysed the tonsillar myeloid compartment in healthy subjects across a wide range of age (64% male; age range: 3 - 85 years) and compared its composition to the peripheral blood. We could observe a strong accumulation of all granulocyte subsets in the aging tonsil, which was most pronounced for basophils and mast cells. On functional level, an increase of CD163 and CD206 expression among monocytes and an increase of neutrophils expressing the inhibitory FcγRIIb correlated with increasing age. While the age-related shift of the leukocyte composition towards monocytes in blood is not reflected in tonsils, the increasing immunoregulatory phenotype of tonsilar monocytes is potentially counteracting the phenomenon of inflammaging at higher age.